2020
DOI: 10.21608/scvmj.2020.145315
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Microorganisms Associated to She Camels’ Subclinical and Clinical Mastitis in South Sinai, Egypt

Abstract: The current study aimed to detect microbial causes of she camel's subclinical and clinical mastitis and antibiotic sensitivity test for some bacterial isolates. A total of 196 milk samples were collected from mastitic and apparent healthy she camels, milk samples of apparent healthy she camels were examined by California mastitis test for detection of subclinical mastitis. All samples were cultivated on different media for detection of bacteria and fungi causing mastitis. S. aureus and Acholeplasma were subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
(4 reference statements)
1
3
1
Order By: Relevance
“…The results showed that E. coli was isolated using conventional culture methods from 25.6 and 19.7% of the examined clinically and sub-clinically mastitic camel’s milk. These findings are lower than those previously obtained by Abo Hashem et al [ 40 ], who reported that E. coli was the most predominant isolated bacteria from she-camel’s milk with isolation rates of 35.4 and 27% from apparently healthy and mastitic she-camel’s milk, respectively. Concerning the isolation of E. coli from the fecal samples, our results showed that E. coli was isolated from 44.4 and 12.3% of the examined fecal samples collected from diarrheic camels and apparently healthy she-camels, correspondingly, as shown in Table 3 .…”
Section: Discussioncontrasting
confidence: 76%
“…The results showed that E. coli was isolated using conventional culture methods from 25.6 and 19.7% of the examined clinically and sub-clinically mastitic camel’s milk. These findings are lower than those previously obtained by Abo Hashem et al [ 40 ], who reported that E. coli was the most predominant isolated bacteria from she-camel’s milk with isolation rates of 35.4 and 27% from apparently healthy and mastitic she-camel’s milk, respectively. Concerning the isolation of E. coli from the fecal samples, our results showed that E. coli was isolated from 44.4 and 12.3% of the examined fecal samples collected from diarrheic camels and apparently healthy she-camels, correspondingly, as shown in Table 3 .…”
Section: Discussioncontrasting
confidence: 76%
“…Many studies focus on camel's mastitis and show that about 25% were subclinical cases in Ethiopia (12), 16.6% in Saudi Arabia (42), and 11.7% in the United Arab Emirates (43). Finally, 25.8% in Egypt (41) were associated with different bacterial isolates (17,37). This percentage was near to that recorded in our study, reaching about 26% from all milk samples, which indicates highly spread of Mycoplasma infection in milk.…”
Section: Discussionsupporting
confidence: 55%
“…Bacterial camel's mastitis can be either clinical and/or subclinical. The subclinical mastitis was most crucial as it did not show any clinical signs and did not cause any noticeable change in the udder or milk, farther that subclinical mastitis comes before clinical mastitis and may take a long period to diagnose, which causes the animals' source for environmental contamination and spread of disease for other animals (40,41). Many studies focus on camel's mastitis and show that about 25% were subclinical cases in Ethiopia (12), 16.6% in Saudi Arabia (42), and 11.7% in the United Arab Emirates (43).…”
Section: Discussionmentioning
confidence: 99%
“…Pal et al, 2015 suggested a role of Candida in mastitis of one humped camel in Ethiopia by applying standard mycological techniques [ 27 ]. The genus Aspergillus was the most predominant fungi followed by Candida in she camel mastitis in Egypt in a culture-dependent study [ 60 ]. These two genera were also isolated from goat subclinical and clinical mastitis [ 61 – 63 ].…”
Section: Discussionmentioning
confidence: 99%